Informasi dan Pengetahuan sebagai Akses Menuju Kemakmuran Bersama : sebuah narasi dari pandangan Habermas hingga Knowledge Management - Alam, Umar Falahul (STAIN Ponorogo, 2010)
Information and knowledge which are transformed to anyone will provide tremendous value. When someone is born in the world he has a variety of rights that should not be act, including the right to obtain information and knowledge. The existence of two elements will help an individual or a group discover the identify of the nation that can provide great benefits in the activities of their lives, wether social, political, economic, business or intellectual. In addition, it will culminate in a the highest stage of wisdom. Someone who is able to occupy these domains is believed to be the personally and socially enlightened individual.